Проблемы и противоречия гносеологии образования - Пономарев, Александр Семенович; Харченко, Алла Александровна (Institutul Internațional de Management Imi-Nova, 2018)
It is shown that the innovative nature of the development of human civilization has led to new requirements for the education system. To meet them, a philosophical understanding of the essence of the phenomenon of education, its goals and role, the ways of development is necessary. These circumstances caused an intensive development of the philosophy of education as a specific social institution. In the general structure of the philosophy of education,a special place belongs to his epistemology. It is it that contributes to the increase in the effectiveness of the educational and cognitive activity of students in the conditions of a constantly growing volume of scientific and technical knowledge. However, the epistemology of education inherent specific problems and contradictions, the resolution of which is necessary to build a new education paradigm that would focus not on memorizing information, but on its understanding. One of them is that education is an object of study of epistemology, and one of its main tools. Another contradiction should be considered the dominance of rational forms of cognition and a certain disregard for the possibilities of its emotional forms. Essential is the contradiction, which consists in the students not knowing the outside world itself, but information about it, which generates the loss of critical thinking and the desire for a comprehensive analysis of objects and the phenomenon of cognition.
Keywords: philosophy of education; gnoseology; contradictions; rational forms of cognition; critical thinking; філософія освіти; гносеологія; протиріччя; раціональні форми пізнання; критичне мислення